2011
DOI: 10.1103/physrevlett.106.117602
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Magnetism and Superconductivity in the Iron-Based CompoundCs0.8(FeSe0.98)2

Abstract: We report on muon-spin rotation and relaxation (µSR), electrical resistivity, magnetization and differential scanning calorimetry measurements performed on a high-quality single crystal of Cs0.8(FeSe0.98)2. Whereas our transport and magnetization data confirm the bulk character of the superconducting state below Tc = 29.6(2) K, the µSR data indicate that the system is magnetic below TN = 478.5(3) K, where a first-order transition occurs. The first-order character of the magnetic transition is confirmed by diff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
177
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(183 citation statements)
references
References 23 publications
6
177
0
Order By: Relevance
“…42), or more recently the iron arsenides 11,12,15,17,19,20,[43][44][45][46][47] and iron selenides. [48][49][50] The neutron diffraction experiments were performed at the thermal four-circle single-crystal diffractometer TRICS at the spallation neutron source SINQ at PSI. A pyrolytic 184509-2 graphite (PG-002) monochromator was used with neutron wavelength λ = 2.4Å.…”
Section: Methodsmentioning
confidence: 99%
“…42), or more recently the iron arsenides 11,12,15,17,19,20,[43][44][45][46][47] and iron selenides. [48][49][50] The neutron diffraction experiments were performed at the thermal four-circle single-crystal diffractometer TRICS at the spallation neutron source SINQ at PSI. A pyrolytic 184509-2 graphite (PG-002) monochromator was used with neutron wavelength λ = 2.4Å.…”
Section: Methodsmentioning
confidence: 99%
“…6 These include the presence of the iron vacancies and their ordering, the antiferromagnetically ordered insulating phases and a very high Néel transition temperature. [7][8][9][10][11] Nickel pnictides have recently attracted a lot of attention, 12 despite of the low critical superconducting temperature, much lower than in iron based pnictides. The cause of such significant distinction in T c value is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…The recent discovery of block checkerboard antiferromagnetic order of superconducting materials A x Fe 2−y Se 2 , A = K, Rb, Cs and Tl) has invoked considerable debate in the scientific community. [1][2][3][4][5][6] It was shown that the appearance of antiferromagnetism is a consequence of the Fe vacancy ordering. 7,8 These unique properties among the superconductors opened a question whether Fe vacancies stabilize or destroy the superconductivity.…”
mentioning
confidence: 99%